2012
DOI: 10.1038/ncb2455
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 activation mediates Twist1-induced cancer cell migration

Abstract: Epithelial-mesenchymal transition (EMT), which is characterized by the suppression of the adhesion protein E-cadherin, is a crucial process that promotes metastasis and stem-like properties of cancer cells. However, the dissociation of cellular aggregates is not sufficient to explain why cancer cells move, and the motile nature of cancer cells undergoing EMT remains elusive. Here, we identify a mechanism in which the EMT inducer Twist1 elicits cancer cell movement through activation of RAC1. Twist1 cooperates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
200
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(211 citation statements)
references
References 44 publications
6
200
1
Order By: Relevance
“…Modeling the mRNA degradation with the let-7 sensors suggest that the effect of a specific let-7 miR on a particular target mRNA depends on the degree of miR-mRNA complementarity and on the ratio of particular let-7 miR and its mRNA target. Although the let-7 family members are often considered to have redundant functions (21), studies in squamous cell carcinomas of the head suggest that let-7b inhibits proliferation, let-7d represses epithelial to mesenchymal transition, and let-7i mainly inhibits mesenchymal cell movement (46)(47)(48). Our observations support the possibility that the let-7 family members exhibit target selectivity and thus might promote different cell fates even when expressed in the same cell type.…”
Section: Discussionsupporting
confidence: 74%
“…Modeling the mRNA degradation with the let-7 sensors suggest that the effect of a specific let-7 miR on a particular target mRNA depends on the degree of miR-mRNA complementarity and on the ratio of particular let-7 miR and its mRNA target. Although the let-7 family members are often considered to have redundant functions (21), studies in squamous cell carcinomas of the head suggest that let-7b inhibits proliferation, let-7d represses epithelial to mesenchymal transition, and let-7i mainly inhibits mesenchymal cell movement (46)(47)(48). Our observations support the possibility that the let-7 family members exhibit target selectivity and thus might promote different cell fates even when expressed in the same cell type.…”
Section: Discussionsupporting
confidence: 74%
“…Twist1 is an established repressor of E-cadherin gene transcription during EMT, 14,15 and it directly induces N-cadherin expression in PC cells. 16 Moreover, Twist1 has been shown to induce RAC1 activity 22 and formation of invadopodia in cancer cells. 24 The regulatory regions of the Twist1 gene contain the g-interferoneactivated sequence, 85 a binding element shared by Stat3 and Stat5a/ b, and Stat3 has been shown to up-regulate Twist1 gene expression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…61 Additionally, Rho family GTPases are well recognized for their complex interaction networks and multiple roles played in regulation of actin cytoskeleton assembly. 62 It has also been reported that two of the Rho family GTPases, cell division control protein 42 (Cdc42) and Rac1, can regulate cell motility, [63][64][65] phagocytosis, 66 and macropinocytosis. 67 Therefore, we hypothesized that electrotransfection could lead to actin remodeling and enhance macropinocytosis through activation of Cdc42 and Rac1.…”
Section: Dna Uptake By Electrotransfection-induced Macropinocytosis Imentioning
confidence: 99%